Evaluation of Opportunities and Challenges for Cooperatives in Development HR in the Market 4.0 Competition War Environment towards Indonesian Economy 2045 - Samad, Abdul Wahab; Muhammad Ishaq; Dominica Dini Afiat (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to conduct a study of the opportunities and challenges of cooperatives in the industrial era 4.0 by strengthening the role of human resource management in facing changes in the market environment facing competition war 4.0 in the Indonesian economy in 2045 which causes changes in all aspects of digitalization that occur in cooperative organizations. The changes that occur also require business intelligence in evaluating high-tech advances in the exchange of knowledge related to design and innovation and information obtained from supplier and customer behavior which will be continuously communicated in industry 4.0. The research method in this study is a troubling method which examines cause and effect relationships in depth, listening to input from various parties and finding appropriate solution ideas through studying narratives expressed qualitatively. The results of this research found that cooperative development in Indonesia still needs to be improved to become stronger in planning and financing. This development will be the basis for the Indonesian economy to achieve the goal of an economy based on mutual cooperation in 1945.